Exploring the Rule of âTaâzÄ«r is Left to the Discretion of the Rulerâ and a Case Study of Discretionary Prison Sentence - Ã˜Â´Ã˜Â§Ã›ÂŒÃ™Â‚, Ã™Â…Ã™Â‡Ã˜Â¯Ã›ÂŒ; Ã˜Â´Ã˜Â§Ã›ÂŒÃ™Â‚, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã˜Â±Ã˜Â¶Ã˜Â§ (Ø§ÙØªØ´Ø§Ø±Ø§Øª Ø¯Ø§ÙØ´Ú¯Ø§Ù ÙØ±Ø¯ÙØ³Û Ù Ø´ÙØ¯)
Defining the type of punishment is an important matter about taâzÄ«r (discretionary punishment) which, in turn, is an important and everyday issue in the judicial system. Some scholars believe that according to the rule of âtaâzÄ«r is left to the discretion of the rulerâ, the ruler enjoys considerable leeway in deciding an appropriate form as well as the amount of punishment, while other scholars say that the freedom given to a judge through this rule is restricted to the amount of punishment and the form of punishment is out of his jurisdiction. The first group of scholars, in addition to the lexical references, has resorted to explicit hadiths received regarding the issue, as well as the ordinances that show the vast scope of the authority a ruler possesses. The paper, after criticizing the above-mentioned reasons, presents evidence from hadiths to refute the wide authority of a ruler claimed by these scholars. Moreover, even supposing such wide authority of a ruler, the punishments like imprisonment are inconsistent with some principles and general rules like wizr (personal responsibility of offence) and âtaâzÄ«r must be more lenient than á¸¥addâ.